Prototipe Proteksi Motor 3 Fasa Menggunakan Rele PFR NJYB315 - Syaprudin; Yonda Nugraha; Aripin Triyanto (CV. Multi Kreasi Media, 2023)
The causes of damage that occurs in an electrical circuit are short circuits and troubleshooting from external and internal disturbances. So that damage does not occur in the circuit and damage the installed system, it is necessary to have protection installed in the circuit. The protection can be applied at the input and output of a circuit. The method used is to design a protection prototype and load simulation using a 3 phase motor. The use of the method is to design, determine the relay with the load capacity of the 3 phase motor used and carry out load testing in stages. The purpose of the design is to determine the performance of the NJYB315 relay under the influence of disturbances generated in the circuit under normal and loaded conditions. The data generated in the design is that the relay does not work under normal conditions when the voltages R, S and T are supplied with a voltage of 380 V, the relay does not work. When a loss occurs or a single phase is cut off, the relay works to cut off the current flowing in the circuit. When a trip occurs, the relay works to cut off the input current flowing to the motor and this condition proves that the relay is working properly.